Time Slows Down during Accidents - Arstila, Valtteri (Frontiers in Psychology, 2012)
The experienced speed of the passage of time is not constant as time can seem to fly or slow down depending on the circumstances we are in. Anecdotally accidents and other frightening events are extreme examples of the latter; people who have survived from accidents often report altered phenomenology including how everything appeared to happen in slow motion. While the experienced phenomenology has been investigated, there are no explanations about how one can have these experiences. Instead, the only recently discussed explanation suggests that the anecdotal phenomenology is due to memory effects and hence not really experienced during the accidents. The purpose of this article is i) to reintroduce the currently-forgotten comprehensively altered phenomenology that some people experience during the accidents, ii) to explain why the recent experiments fail to touch the issue at hand, and iii) to suggest a new framework to explain what happens when people experience time slowing down in these cases. The presented solution is realistic in a sense that it maintains that sometimes people really do have such experiences.